SEJARAH DAN PROBLEMATIKA DAKWAH RASULULLAH SAW - Firmansyah, M Feri (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2020)
Rasulullah SAW was known as a preacher, leader and teacher who became a role model for Muslims. During the preaching of the Prophet Muhammad passed through two periods, namely the Mecca period and the Medina period. Both of these periods have characteristics from the side of mad'u, if the Mecca period had one type of mad'u, only the Quraysh disbelievers would deny Allah. Whereas in the Medina period the characteristics of mad'u were more religious which consisted of hypocrites, Jews and believers (Ansar and Muhajirin). The propaganda of Madinah Rasulullah peace be upon him can be applied in Indonesia, namely by dominating national markets and national politics (becoming head of the State). Because if a preacher can master this, then he will be able to apply the method of hasanah mauidzah, wisdom and reciprocity in overlap.